Targeting the IDO1 pathway in cancer: from bench to bedside - Liu, Ming; Wang, Xu; Wang, Lei; Ma, Xiaodong; Gong, Zhaojian; Zhang, Shanshan; Li, Yong (Journal of hematology and oncology, 2018)
Indoleamine 2, 3-dioxygenases (IDO1 and IDO2) and tryptophan 2, 3-dioxygenase (TDO) are tryptophan catabolic enzymes that catalyze the conversion of tryptophan into kynurenine. The depletion of tryptophan and the increase in kynurenine exert important immunosuppressive functions by activating T regulatory cells and myeloid-derived suppressor cells, suppressing the functions of effector T and natural killer cells, and promoting neovascularization of solid tumors. Targeting IDO1 represents a therapeutic opportunity in cancer immunotherapy beyond checkpoint blockade or adoptive transfer of chimeric antigen receptor T cells. In this review, we discuss the function of the IDO1 pathway in tumor progression and immune surveillance. We highlight recent preclinical and clinical progress in targeting the IDO1 pathway in cancer therapeutics, including peptide vaccines, expression inhibitors, enzymatic inhibitors, and effector inhibitors.